Informational technology for the complex estimation of the biological organism ageing processes - Гернет, Надежда Дмитриевна; Божков, Анатолий Иванович (Eastern-European Journal of Enterprise Technologies, 2012)
The issues of the creation of information technology for the complex estimation of the aging processes of the biological organisms (biological systems) are viewed in the present abstract. The information technology is based on the expert procedure, which puts into practice the idea of the hierarchy analysis method. Information technology allows to determine the most informative quantitative aging characteristics of the considered class of biological organisms and on their basis to determine the integrative characteristics of the system aging of biological organisms, to fullfil the complex estimation of processes of aging on the whole. The analysis of the time history of the complex estimation of aging processes of a given organism will allow to estimate the rate of the system aging of this organism on the whole, and the analysis of the time history of the integral features of a separate subsystem, which is very relevant to build the diagnostic system of aging. The possibility of the periodic estimation of aging of a biological organism will allow to create the system of regulating the aging processes with the aim of increasing the working capacity, rejuvenation and prolongation of active life of a man